Safety Indices of Ultrasound: Adherence to Recommendations and Awareness During Routine Obstetric Ultrasound Scanning - Drukker, Lior; Droste, Richard; Chatelain, Pierre; Noble, J. Alison; Papageorghiou, Aris T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To analyze bioeffect safety indices and assess how often operators look at these indices during routine obstetric ultrasound.Materials and Methods Automated analysis of prospectively collected data including video recordings of full-length ultrasound scans coupled with operator eye tracking was performed. Using optical recognition, we extracted the Mechanical Index (MI), Thermal Index in soft tissue (TIs), and Thermal Index in bone (TIb) values and ultrasound mode. This allowed us to report the bioeffect safety indices during routine obstetric scans and assess adherence to professional organization recommendations. Eye-tracking analysis allowed us to assess how often operators look at the displayed bioeffect safety indices.Results A total of 637 ultrasound scans performed by 17 operators were included, of which 178, 216, and 243 scans were first, second, and third-trimester scans, respectively. During live scanning, the mean and range were 0.14 (0.1 to 3.0) for TIb, 0.2 (0.1 to 1.2) for TIs, and 0.9 (0.1 to 1.3) for MI. The mean and standard deviation of TIb were 0.15 ± 0.03, 0.23 ± 0.09, 0.32 ± 0.24 in the first, second, and third trimester, respectively. For B-mode, the highest TIb was 0.8 in all trimesters. The highest TIb was recorded for pulsed-wave Doppler mode in all trimesters. The recommended exposure times were maintained in all scans. Analysis of eye tracking suggested that operators looked at bioeffect safety indices in only 27 (4.2 %) of the scans.Conclusion In this study, recommended bioeffect indices were adhered to in all routine scans. However, eye tracking showed that operators rarely assessed safety indices during scanning.
Keywords: ultrasound safety; doppler ultrasound; thermal index; output display standard; eye tracking